Enhancement of tooth eruption by using amniotic stem cells (Immunohistochemical study of VEGF marker) - Athraa Y Al- Hijazi; Lubna K Jassim (College of Dentistry/ University of Baghdad, 2014)
Background: Tooth eruption is a localized process in the jaws which exhibits precise timing and bilateral symmetry. Develop within the jaws and their eruption is a complex infancy process during which they move through bone to their functional positions within the oral cavity. For species with more than one set of teeth, eruption of the second set also accomplishes. The key to the successful clinical management of tooth eruption consists of understanding that this process consists largely of the local regulation of alveolar bone metabolism to produce bone resorption in the direction of eruption and shift and formation of bone at the opposite side.The amniotic sac contains a considerable quantity of stem cells. These amniotic stem cells are able to differentiate into various tissues, which used in many field. Vascular endothelial growth factor (VEGF) is an important angiogenic factor reported to induce migration and proliferation of endothelial cells, enhance vascular permeability, and modulate thrombogenicity. VEGF expression in cultured cells (smooth muscle cells, macrophages, endothelial cells) is controlled by growth factors and cytokines. The aim of this study was to study the administration of cell molecules of (Chorion, Amnion and Amniotic fluid) around developing mouse tooth and studying the expression of VEGF marker. Materials and Methods: forty eight albino Swiss mice of one day old age injected with isolated amniotic stem cells in the anterior region of maxilla (incisors area) other 16 mice injected with saline represents control. Sacrifice 4 mice for each period (4, 7, 10, and 13) day old age. The result were studied histologically and immunohistochemistry. Results: VEGF marker localized and identified in 3 areas; pulp, P.D.L, and Bone. In pulp. The mean value of positive VEGF expression showed to be highest in Amnion group in comparison to the other studied groups. The marginal mean value of all periods reported to be highest in Amnion groups followed by Chorion group. The period 10 day showed highest marginal means value for positive VEGF expression for all groups. In P.D.L. area Amniotic fluid records the highest mean and marginal mean value specifically at day-10 in comparison to other studied groups. In Bone area Amniotic fluid records the highest mean and marginal mean value among the studied groups followed by Chorion group. Period 7-day and 10-day shows high mean value for VEGF expression. Coincidence test for VEGF marker illustrates to be affected by Amniotic fluid application in P.D.L. and in bone area while Amnion and Chorion application showed to be concerned with pulp. Conclusion. It reported that amniotic fluid application affected on expression of VEGF in P.D.L and bone while amnion and chorion showed to affect on expression of VEGF in pulp.The present study highlighted on clinical and researcher application of Amniotic fluid and Chorion for supplement of stem cell in dental tissue engineering or even in other body tissues.